Evaluasi Pengelolaan Sumber Daya Teknologi Informasi (IT Resource Management) dengan Menggunakan Framework COBIT 5 (Studi Kasus : PT. Infomedia Nusantara) - Alvian Restu Naspati; Suprapto Suprapto; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
PT. Infomedia Nusantara is a company engaged in the field of CRM and BPM. PT. Infomedia Nusantara utilizes information technology to help companies achieve their goals. Because there are still deficiencies in the management of IT assets, as well as the management of human resources that support IT operations, therefore the capability level analysis with qualitative method using the COBIT 5 framework uses process EDM04 (asset resource optimization), APO07 (manage human resources), BAI09 (manage assets), and DSS01 manage operation). The data were collected using data triangulation technique by observation, interview, and assessment with assessment sheet. After the assessment with respondens, general manager network and IT infrastructure, deputyGM human resource, dan manager IT operation which choosen based on RACI Chart in COBIT 5,it can be seen that the level achieved by PT. Infomedia Nusantara on process EDM04, APO07, BAI09, and DSS01 is at level 3. There is a GAP of 1 level from each sub-domain because the desired level of the company is level 4. The recommendation that will be given is focused on making process measurement documents from each sub-domain and control limits